Comedy Central stand-up vault. 1 [videorecording (DVD)] - Cook, Dane; Gaffigan, Jim; Regan, Brian, 1958-; Black, Lewis, 1948-; Gottfried, Gilbert, 1955-2022; Iglesias, Gabriel, 1976-; White, Ron, 1956-; Dunham, Jeff, 1962- (Paramount Pictures, 2015)
A collection of stand-up comedians discussing everything from their deep hatred of bottled water to theories about the five levels of fatness and other aspects of everyday life.